2021
DOI: 10.3390/plants10081713
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Polyphenol Biosynthesis by Calli Cultures, Suspension Cultures and Wild Specimens of the Medicinal Plant Ligaria cuneifolia (Ruiz & Pav.) Tiegh. (Loranthaceae). Analysis of Their Biological Activity

Abstract: Ligaria cuneifolia (R. et P.) Tiegh. (Loranthaceae) is a South American hemiparasitic species with antioxidant, antitumoral, antimicrobial, and antilipidemic activities attributed to its polyphenolic content. We studied the polyphenolic pattern of L. cuneifolia during different phenological stages: flowering, fruiting, and post-fruiting. The highest total phenolic content was found in stems at post-fruiting (214 ± 12.1 mg gallic acid eq·g−1 DW) and fruiting (209 ± 13.7 mg gallic acid eq·g−1 DW), followed by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…[55,56] Betulin and betulinic acid are also obtained from the aerial parts by a dichloromethane extraction directly [57] or by maceration with ethanol followed by vacuum liquid chromatography on silica gel and elution with a stepwise gradient of hexane/diethyl ether/methanol. [58] Tyramine is also found in L. cuneifolia aerial parts, and this is particularly important since this species is mainly used as a hypotensive agent. An extensive study performed in Argentina, in the provinces of Córdoba, Mendoza, San Juan, Catamarca, Salta and Entre Ríos on 12 different hosts (belonging to the Zygophyllaceae, Anacardiaceae, Fabaceae, Mimosaceae, Santalaceae families) confirmed that specimens developing on Geoffroea decorticans contain higher levels of this substance in the stems (120-360 mg/ 100 g dried material) while leaf content is more variable (40-240 mg/100 g).…”
Section: Ligaria Cuneifoliamentioning
confidence: 99%
See 4 more Smart Citations
“…[55,56] Betulin and betulinic acid are also obtained from the aerial parts by a dichloromethane extraction directly [57] or by maceration with ethanol followed by vacuum liquid chromatography on silica gel and elution with a stepwise gradient of hexane/diethyl ether/methanol. [58] Tyramine is also found in L. cuneifolia aerial parts, and this is particularly important since this species is mainly used as a hypotensive agent. An extensive study performed in Argentina, in the provinces of Córdoba, Mendoza, San Juan, Catamarca, Salta and Entre Ríos on 12 different hosts (belonging to the Zygophyllaceae, Anacardiaceae, Fabaceae, Mimosaceae, Santalaceae families) confirmed that specimens developing on Geoffroea decorticans contain higher levels of this substance in the stems (120-360 mg/ 100 g dried material) while leaf content is more variable (40-240 mg/100 g).…”
Section: Ligaria Cuneifoliamentioning
confidence: 99%
“…[55,56] When studying organs (stems, leaves and fruits) and phenological stages (flowering, fruiting, post-fruiting), it was verified that stems and leaves exhibit the highest polyphenolic values, especially in the fruiting and post-fruiting stage, which supports the traditional use of these organs. [55,56,58] Efforts have been directed to establish in vitro L. cuneifolia cultures. In this sense, polyphenol profile is quite similar to the adult plant, with quantitative variations.…”
Section: Ligaria Cuneifoliamentioning
confidence: 99%
See 3 more Smart Citations